Gambaran tingkat pengetajuan dan sikap seks pranikah remaja pada siswa kelas X - Nurul Furqoni; Dyah Noviawati Setya Arum; Dwiana Estiwidani (Jurnal Kesehatan Ibu dan Anak, 2015)
The women aged 16-20 years in DIY who had given birth to1-2 children as much as 56.10% and the majority due to premarital sexual behavior. Behavior is influenced by several factors, including the knowledge and attitude of a person.Gedongtengen is a region who had high free sex lifestyle, SMK Negeri 1 Yogyakarta is the only school at the high school level in Gedongtengen, so that possible exposure to the influence of free sex in their environment. This study aims to describe the level of knowledge and attitude of adolescent premarital sex in class X SMK N 1 Yogyakarta. Research location in SMK Negeri 1 Yogyakarta.The subjects(respondents) were 189 students in grade X. This type of research is a descriptive cross-sectional design.After processing the data, the majority of students have a good knowledge level (86.24%), and be not support (positive) pre-marital sex (58.20%).Highest level of knowledge is in the definition of reproductive health component categories (97.35%). Half male students have a good knowledge level. The majority female students have a good knowledge level (87.43%). Half male students have positive attitude and the majority of female students have positive attitude (50.47%). The majority of students have a primary source of reproductive healthinformation by the Internet (58.20%).Conclusion of the study is that themajority of respondents have a good level of knowledge and positive attitude of premarital sex.